Rare disease landscape: will the blockbuster model be replaced?. (August 2014) - Stephens, Jonathan; Blazynski, Christine
<x xml:space="preserve">Abstract</x> Introduction: The pharmaceutical industry entered the 21st century buoyed by a series of mega hits that carried it through the nineties on a wave of promise. More recently, the perceived wisdom came that the age of the mega-selling, mass-marketed drug was over; no more Prozacs, Lipitors or Viagras. With the 'blockbuster bubble' seemingly burst and patent protection giving way to huge rises in generic competition, the pharmaceutical industry would now seek to sustain itself by focusing on niche markets; high-value drugs for rare diseases of low prevalence, but for which a rich return on investment could be reaped. Is this picture correct? Areas covered: This analysis looks across the rare diseases to determine the top disease targets, the most active drug developers and density by drug development phase, using data from a proprietary pipeline drug database. Examples of different development strategies (orphan expansion to other orphan designations; mainstream disease to orphan; orphan expansion to mainstream) are also highlighted. Expert opinion: The growing trend in orphan drug designations and approvals of drugs to treat the rare diseases is likely unsustainable, largely due to pressure on health care bodies and governments to reduce costs at a time of widespread austerity. As more targeted therapies are developed along with companion diagnostics, diseases will become more segmented – to the point where a once prevalent disease meets the rare disease designation. Cancer drug development is already demonstrating this trend.